PENGARUH PAD, DAU, DAK DAN DBH TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL - Heliyanto, Firnandi; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Local expenditure according to Decree of Ministry of Home Affairs No. 29 of 2002 is all local cash expenditures in certain fiscal year periods become the local burden. Meanwhile, according to the Regulations No. 23 of 2004 states that local expenditure is the obligation of local government which is recognized as the deduction of net assets value in the relevant fiscal year. Based on the PP Sap No. 24 of 2005 expenditure consists of operating expenditure, capital expenditure, unforeseen expenditure, and transfer. This research is meant to analyze the influence of Local own source Revenues (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH), to the Budget Allocation of Capital Expenditure on Cities / Districts in East Java. This research is carried out by using the secondary data. The data which has been applied in this research is the 2012-2014 data which have been taken from districts or cities in East Java Province which have been issued by the Directorate General of Financial Balance of Local Government Finance Department. The data analysis technique has been done by using quantitative analysis. The results of the research show that the local own source revenue (PAD), General Allocation Fund (DAU), and Profit Sharing Fund (DBH) have significant and positive influence to the Allocation of Capital Expenditure. Meanwhile, the Special Allocation fund (DAK) does not have any significant and positive influence to the allocation of capital expenditure.Keywords: Local Own Resources (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH), Capital Expenditure.